Pelatihan Branding dan Komunikasi Visual bagi Siswa SMK Al-Islah Surabaya - Mohamad Yusak Anshori; Azmil Chusnaini; Reizano Amri Rasyid (Abimanyu : Jornal of Community Engagement, 2026)
This community service program aims to enhance vocational high school students entrepreneurial competencies, particularly in the creative industry sector, through the implementation of integrated marketing strategy training. The program was conducted at SMK Al-Islah Surabaya, focusing on Visual Communication Design (VCD) expertise, to bridge the gap between students' technical design skills and their understanding of strategic marketing aspects. The method included needs assessment, material preparation, interactive three-day training sessions, and comprehensive evaluation. The core materials delivered were Value Proposition, 5A Consumer Behavior Analysis, and SWOT Analysis. Evaluation results indicated a significant improvement in students' marketing concept comprehension, increased active participation in practical sessions, and the development of entrepreneurial mindsets and professional attitudes. This program demonstrates that an applied, participatory educational approach effectively enhances vocational students' readiness for the job market while fostering early innovation in the creative industry sector